1999
DOI: 10.1046/j.1365-2141.1999.01611.x
|View full text |Cite
|
Sign up to set email alerts
|

High levels of lung resistance related protein mRNA in leukaemic cells from patients with acute myelogenous leukaemia are associated with inferior response to chemotherapy and prior treatment with mitoxantrone

Abstract: Summary. Expression of the mdr1 (multidrug resistance), mrp (multidrug resistance associated protein), and lrp (lung resistance related protein) genes is associated with transport related MDR (multidrug resistance). We quanti®ed mRNA levels of these genes using competitive reverse transcription polymerase chain reaction (RT-PCR) in 128 samples of leukaemic cells from 92 patients with acute myelogenous leukaemia (AML).There was a wide variation between the samples in mRNA levels of all three genes. The mean mdr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Therefore, LRP mRNA expression was particularly influential in outcomes following induction chemotherapy in AML patients. This correlation between LRP expression and treatment outcome is consistent with suggestions that chemosensitive leukemic cells have low LRP mRNA levels in AML (10, 13). …”
Section: Discussionsupporting
confidence: 90%
“…Therefore, LRP mRNA expression was particularly influential in outcomes following induction chemotherapy in AML patients. This correlation between LRP expression and treatment outcome is consistent with suggestions that chemosensitive leukemic cells have low LRP mRNA levels in AML (10, 13). …”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown conflicting results with regards to MDR1, MRP and LRP/MVP upregulation at relapse, probably because they were often performed in a heterogeneous pool of diagnostic, relapse and secondary AML samples (Table 5). 12,16,29,[52][53][54][55][56][57][58] It has often been suggested that MDR1 expression at the time of relapse is higher as compared to diagnosis. 33,[59][60][61][62][63][64][65] In the present study, we did not find a higher level of MDR1 mRNA, nor P-glycoprotein function and expression at relapse or in refractory disease in these AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…A leukemia type repeatedly reported to express MVP in a substantial proportion of patients at diagnosis is acute myeloid leukemia (AML) [81][82][83][84][85][86][87][88][89][90][91][92]. One problem with the data regarding MVP expression in AML is the profound variation in the percentage of MVP-positive AML cases reported, varying between 34% [81] and 69% [93] when using immunocytochemistry but reaching values of up to 91% by RT-PCR [94] and down to 26% by flow cytometry [95].…”
Section: Haematological Malignanciesmentioning
confidence: 91%
“…One problem with the data regarding MVP expression in AML is the profound variation in the percentage of MVP-positive AML cases reported, varying between 34% [81] and 69% [93] when using immunocytochemistry but reaching values of up to 91% by RT-PCR [94] and down to 26% by flow cytometry [95]. Several studies found an association between MVP expression and therapy resistance [81][82][83][84] as well as in some cases also patient prognosis [90][91][92], whereas others found no association with either parameter [85][86][87][88][89]. In vitro MVP expression did neither correlate with daunomycin accumulation nor cytotoxicity of patient-derived AML cells [96].…”
Section: Haematological Malignanciesmentioning
confidence: 95%